Brand Ambassador AESPA sebagai Penunjang Brand Image Nabati Richoco - Renwarin, Angie Veronica; Pribadi, Muhammad Adi (Kiwari, 2026)
This study explores how K-Pop brand ambassadors contribute to brand image amidst the trend of utilizing K-Pop idols in digital marketing communication strategies. This study begins with the phenomenon of utilizing collaboration campaigns, exclusive photocards, and fan engagement activities on social media to examine the emotional closeness between brands and fans. The purpose of this study is to understand the presence of Aespa as a brand ambassador to support the brand image of Nabati Richoco among K-Pop fans exposed to the collaboration campaign. The study uses a qualitative approach with a phenomenological method to explore the direct experiences of Aespa fans who learned about the collaboration, saw promotional materials, and purchased Aespa x Richoco products. Data were obtained through in-depth interviews with informants selected purposively based on their involvement. The analysis focuses on brand image factors (Strength of Brand Association, Favorability of Brand Association, and Uniqueness of Brand Association) and VisCAP indicators (visibility, credibility, attraction, power) to see how brand ambassadors are able to shape public perception of the brand image. The results show that brand collaborations, iconic jingles, and photocards are the main reasons why fans purchase products. Penelitian ini berisi bagaimana brand ambassador K-Pop berkontribusi dalam brand image di tengah tren pemanfaatan idol K‑Pop dalam strategi komunikasi pemasaran digital. Penelitian ini berangkat dari fenomena pemanfaatan kampanye kolaborasi, photocard eksklusif, dan aktivitas fan engagement di media sosial untuk melihat kedekatan emosional antara merek dan penggemar. Tujuan penelitian ini untuk memahami kehadiran Aespa sebagai brand ambassador sebagai penunjang citra merek Nabati Richoco di kalangan penggemar K‑Pop yang terpapar kampanye kolaborasi. Penelitian menggunakan pendekatan kualitatif dengan metode fenomenologi untuk menggali pengalaman langsung penggemar Aespa yang mengetahui kolaborasi, melihat materi promosi, dan membeli produk Aespa x Richoco. Data diperoleh melalui wawancara mendalam dengan informan yang dipilih secara purposif berdasarkan keterlibatan mereka. Analisis berfokus pada faktor brand image (Strength of Brand Association, Favorability of Brand Association, dan Uniqueness of Brand Association) dan indikator VisCAP (visibility, credibility, attraction, power) untuk melihat bagaimana brand ambassador seperti mampu membentuk persepsi masyarakat terhadap brand image. Hasil penelitian menunjukkan kolaborasi merek, jingle ikonik, dan photocard, menjadi alasan utama mengapa penggemar membeli produk.